Recent progress in experimental and human disease-associated multi-species biofilms - Bai, Fang (Comput Struct Biotechnol J, 2019)
Human bodies are colonized by trillions of microorganisms, which are often referred to as human microbiota and play important roles in human health. Next generation sequencing studies have established links between the genetic content of human microbiota and various human diseases. However, it remains largely unknown about the spatial organizations and interspecies interactions of individual species within the human microbiota. Bacterial cells tend to form surface-attached biofilms in many natural environments, which enable intercellular communications and interactions in a microbial ecosystem. In this review, we summarize the recent progresses on the experimental and human disease-associated multi-species biofilm studies. We hypothesize that engineering biofilm structures and interspecies interactions might provide a tool for manipulating the composition and function of human microbiota.